2021
DOI: 10.1097/iop.0000000000002051
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Orbital Septal Flap in the Treatment of Moderate and Severe Upper Eyelid Retraction

Abstract: To assess the long-term effectiveness of the orbital septal flap to lengthen the levator muscle in management of moderate and severe upper eyelid retraction.Methods: This study reports 46 eyes of 43 consecutive patients with moderate or severe upper eyelid retraction who were recommended for surgery. The period of the study was between October 2016 and October 2019. All cases were evaluated for eyelid position before and at 3, 6, and 12 months after the operation. Successful outcome was defined as "perfect," "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…After an average of 13 months, the palpebral fissure height was reduced by 2.5 mm and was within 1 mm of the contralateral eyelid in 92% of the patients and they concluded that the turn-over orbital septal flap technique may be a viable option as an autogenous spacer for the treatment of ULR in TED. Recently, a prospective study was done in Vietnam assessing the use of the orbital septal flap technique for patients with moderate to severe UER 22 . They included 46 eyes of 43 consecutive patients with moderate to severe UER with a minimum follow-up period of 12 months (range from 12 to 37 mo).…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…After an average of 13 months, the palpebral fissure height was reduced by 2.5 mm and was within 1 mm of the contralateral eyelid in 92% of the patients and they concluded that the turn-over orbital septal flap technique may be a viable option as an autogenous spacer for the treatment of ULR in TED. Recently, a prospective study was done in Vietnam assessing the use of the orbital septal flap technique for patients with moderate to severe UER 22 . They included 46 eyes of 43 consecutive patients with moderate to severe UER with a minimum follow-up period of 12 months (range from 12 to 37 mo).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Due to the few published papers describing this procedure, the long-term complications are not well described with few articles reporting few patients with recurrence of UER and nonresolve temporal flare in TED patients. Unfortunately, this surgical procedure is not suitable for patients with thin orbital septum, therefore, intraoperative assessment of such finding is important to prevent unwanted outcomes 20–22 …”
Section: Surgical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations